Stationary states of fermions in a sign potential with a mixed vector-scalar coupling - Castilho, W. M. [UNESP]; Castro, A. S. de [UNESP] (Elsevier B.V., 2014)
The scattering of a fermion in the background of a sign potential is considered with a general mixing of vector and scalar Lorentz structures with the scalar coupling stronger than or equal to the vector coupling under the Sturm-Liouville perspective. When the vector coupling and the scalar coupling have different magnitudes, an isolated solution shows that the fermion under a strong potential can be trapped in a highly localized region without manifestation of Klein's paradox. It is also shown that the lonely bound-state solution disappears asymptotically as one approaches the conditions for the realization of spin and pseudospin symmetries. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Sign potential; Spin symmetry; Isolated solution; Effective mass